# Express each of the following as a rational number of the form $\frac{p}{q}$(i) $-\frac{8}{3}+\frac{-1}{4}+\frac{-11}{6}+\frac{3}{8}-3$(ii) $\frac{6}{7}+1+\frac{-7}{9}+\frac{19}{21}+\frac{-12}{7}$(iii) $\frac{15}{2}+\frac{9}{8}+\frac{-11}{3}+6+\frac{-7}{6}$(iv) $\frac{-7}{4}+0+\frac{-9}{5}+\frac{19}{10}+\frac{11}{14}$(v) $\frac{-7}{4}+\frac{5}{3}+\frac{-1}{2}+\frac{-5}{6}+2$

To do:

We have to express the given expressions as a rational number of the form $\frac{p}{q}$.

Solution:

(i) $-\frac{8}{3}+\frac{-1}{4}+\frac{-11}{6}+\frac{3}{8}-3$

LCM of $3, 4, 6$ and $8=24$

$-\frac{8}{3}+\frac{-1}{4}+\frac{-11}{6}+\frac{3}{8}-3 = \frac{(-8)(8)+(-1)(6)+(-11)(4)+3(3)-3(24)}{24}$

$= \frac{-64-6-44+9-72}{24}$

$=\frac{-177}{24}$

$=\frac{-59}{8}$

Therefore,

$\frac{8}{3}+\frac{-1}{4}+\frac{-11}{6}+\frac{3}{8}-3 =\frac{-59}{8}$.

(ii) $\frac{6}{7}+1+\frac{-7}{9}+\frac{19}{21}+\frac{-12}{7}$

LCM of $7, 9, 21$ and $7=63$

$\frac{6}{7}+1+\frac{-7}{9}+\frac{19}{21}+\frac{-12}{7} = \frac{(6)(9)+(1)(63)+(-7)(7)+19(3)+(-12)(9)}{63}$

$= \frac{54+63-49+57-108}{63}$

$=\frac{17}{63}$

Therefore,

$\frac{6}{7}+1+\frac{-7}{9}+\frac{19}{21}+\frac{-12}{7} =\frac{17}{63}$.

(iii) $\frac{15}{2}+\frac{9}{8}+\frac{-11}{3}+6+\frac{-7}{6}$

LCM of $2, 8, 3$ and $6=24$

$\frac{15}{2}+\frac{9}{8}+\frac{-11}{3}+6+\frac{-7}{6}= \frac{(15)(12)+(9)(3)+(-11)(8)+6(24)+(-7)(4)}{24}$

$= \frac{180+27-88+144-28}{24}$

$=\frac{235}{24}$

Therefore,

$\frac{15}{2}+\frac{9}{8}+\frac{-11}{3}+6+\frac{-7}{6} =\frac{235}{24}$.

(iv) $\frac{-7}{4}+0+\frac{-9}{5}+\frac{19}{10}+\frac{11}{14}$

LCM of $4, 5, 10$ and $14=140$

$\frac{-7}{4}+0+\frac{-9}{5}+\frac{19}{10}+\frac{11}{14}= \frac{(-7)(35)+(0)(140)+(-9)(28)+19(14)+(11)(10)}{140}$

$= \frac{-245+0-252+266+110}{140}$

$=\frac{-121}{140}$

Therefore,

$\frac{-7}{4}+0+\frac{-9}{5}+\frac{19}{10}+\frac{11}{14}=\frac{-121}{140}$.

(v) $\frac{-7}{4}+\frac{5}{3}+\frac{-1}{2}+\frac{-5}{6}+2$

LCM of $4, 3, 2$ and $6=12$

$\frac{-7}{4}+\frac{5}{3}+\frac{-1}{2}+\frac{-5}{6}+2= \frac{(-7)(3)+(5)(4)+(-1)(6)+(-5)(2)+(2)(12)}{12}$

$= \frac{-21+20-6-10+24}{12}$

$=\frac{7}{12}$

Therefore,

$\frac{-7}{4}+\frac{5}{3}+\frac{-1}{2}+\frac{-5}{6}+2=\frac{7}{12}$.

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

26 Views